Social Interaction Between Students: Local and International Students’ Experiences at a Turkish University - Aydin, Oya (Journal of International Students, 2020)
The relationship between local and international students has become one of the most important topics in the literature on the internationalization of education; however, these discussions have focused mainly on Western countries and on the perspectives of students who are from similar home countries. The views of students who choose to study abroad in Turkey offer different perspectives. Forty-two international and 35 local students enrolled at Istanbul Bilgi University participated in the study. No students reported an absence of relationships between local and international students; no international participants mentioned loneliness, exclusion, or isolation, even though these concepts appear in many studies of students in Western countries. All students who reported having poor relationships with other groups identified the language barrier as the main cause, and introversion in both local and international students may have prevented meaningful relationships.